Seafloor depressions on the Nigerian margin: Seabed morphology and sub-seabed hydrate distribution. (April 2020) - Taleb, F.; Lemaire, M.; Garziglia, S.; Marsset, T.; Sultan, N.
Abstract: Gas hydrate quantification using acoustic data requires proper knowledge of the mineralogy of their host sediment. In this paper, a petrophysical model allowing GH quantification at sites where mineralogy profiles are absent is proposed. This approach is applied to a high gas flux pockmark system in the Gulf of Guinea where in-situ acoustic and geotechnical measurements together with core measurements could have been correlated and tied to seismic data. Projections of the in-situ measurements on seismic profiles have shown that the study area not only accommodates zones of shallow and dense GH; but also zones where solid hydrate and free gas coexist as well as pockets of free gas. Further analysis of several seismic profiles has allowed illustrating the detailed GH occurrence zone within the study area, estimate its volume and its occupancy ratio of the pockmark. Correlations between GH content and 3D bathymetry sections have allowed to draw a link between different GH contents and the morphology of the pockmark, which also shares similarities with the morphology of the GH occurrence zone it accommodates. Highlights: Mineralogical analysis is essential to estimate GH content using in-situ data. 3D scheme of the pockmark and GH occurrence zone created from seismic data. The geomorphology of the study area is influenced by GH content and distribution.